2018
DOI: 10.1002/jca.21624
|View full text |Cite
|
Sign up to set email alerts
|

The effects of galectin‐3 depletion apheresis on induced skin inflammation in a porcine model

Abstract: Galectin-3 (Gal-3), a β-galactoside-binding lectin that is expressed in mammalian cells, is known to modulate several biological functions such as cell-cell adhesion, macrophage activation, angiogenesis, metastasis, and fibrosis. The goal of this study was to evaluate the ability of Gal-3 depletion apheresis using an adsorption column with immobilized anti-Gal-3-antibody to reduce inflammation induced by Complete Freund's Adjuvant injection in a skin inflammation porcine model. Here, we report that plasma perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…However, a double-blind evaluation of plasmapheresis in ten patients with schizophrenia yielded negative results, and the procedure did not lead to a reduction in psychosis[ 72 ]. As hypercholesterolemia has been treated with plasmapheresis, and recently the therapeutic usefulness of Gal-3 depletion apheresis has been demonstrated in inflammation-mediated disease, targeting Gal-3 molecule may be a useful way to address immunometabolic problems and cognitive deterioration in schizophrenia in the future[ 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a double-blind evaluation of plasmapheresis in ten patients with schizophrenia yielded negative results, and the procedure did not lead to a reduction in psychosis[ 72 ]. As hypercholesterolemia has been treated with plasmapheresis, and recently the therapeutic usefulness of Gal-3 depletion apheresis has been demonstrated in inflammation-mediated disease, targeting Gal-3 molecule may be a useful way to address immunometabolic problems and cognitive deterioration in schizophrenia in the future[ 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, selectively removing Gal-3 through therapeutic apheresis may serve as a potential therapeutic approach. In a porcine model of in ammatory skin induration, Gal-3-speci c therapeutic apheresis resulted in a signi cant, rapid decrease in skin in ammation, as well as faster resolution of skin injury [55]. Apheresis can remove Gal-3 rapidly and e ciently, and can be repeated as needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanistic role of galectin-3 in cGVHD models has not been investigated, so whether galectin-3 is implicated in the causal pathway of cGVHD pathophysiology or serves a secondary marker of inflammation is unknown. This is of particular interest, as animal models have demonstrated that galectin-3 function can be reduced by exposure to modified citrus pectin [ 15 , 16 ], and that galectin-3 can be depleted through therapeutic apheresis [ 17 ], suggesting that galectin-3 could be a potential target for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%